Penerapan E-RUPOCA Terhadap Minat Membaca Anak Desa Cibitung Wetan - Ima Rahmawati; Hana Lestari; Siti Ulfatul Hasanah; Kikih Jakiah Darojah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2022)
One of the innovative steps to help increase children's reading interest is the use of learning media technology and then poured in the form of a digital library called E-Rupoca (Electronic Reading Corner House) through an intermediary computer, laptop or smartphone. This study aims to determine how high the reading interest of Cibitung Wetan children is and also how efficient the digital library is implemented in Cibitung Wetan Village and also to find out how high the interest of Cibitung Wetan children is in using digital libraries compared to ordinary libraries and also what obstacles only encountered in this digital library. The research method used is descriptive qualitative with data collection techniques through observation and interviews. The targets in this research are children in Cibitung Wetan Village. The results of the study show that the implementation of the E-Rupoca digital library has been carried out well although it is still in the process of continuous development and improvement. Then there is an increase in children's interest in reading through the E-Rupoca digital library. The strategy for library programs, both offline and online (digital), is by making weekly visits to the library and monitoring through the website.